VO#032 Valuation of embedded parts and junction box for MEP works rev.02 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the resubmission of the proposal for valuation of embedded parts and junction box for MEP works that includes material and plant supply, transportation, site installation etc. for BRACU new campus project.